A new family with spastic paraplegia type 51 and novel mutations in AP4E1 - Izabela Winkler; Paweł Miotła; Monika Lejman; Aleksandra Pietrzyk; Magdalena Kacprzak; Marcin Kubiak; Agnieszka Sobczyńska-Tomaszewska; Maciej Skrzypczak; Ilona Jaszczuk (BMC, 2021)
Abstract Background Autosomal recessive mutations in the AP-4 (adaptor protein complex 4) complex subunit ϵ − 1 (AP-4E1) gene on chromosome 15q21.2 are known to cause spastic paraplegia 51 (SPG51). The exact phenotype of SPG51 remains poorly characterized, because only a few families have been reported as carriers of the mutation. In addition, a previous study identified an autosomal dominant mutation in the AP4E1 gene as being associated with persistent stuttering. The aim of the current study was to characterize the phenotype of a paediatric patient with an identified novel AP4E1 mutation presenting with significant psychomotor retardation, intellectual disability and paraplegia. Methods Magnetic resonance imaging was used to identify hypoplasia of the corpus callosum. The DNA sample was tested using multiplex ligation-dependent probe amplification (MLPA) and array comparative genomic hybridization (aCGH). In addition, next-generation sequencing (NGS) was performed using the patient's DNA, and Sanger sequencing was performed using that of his family members. Results The phenotype was identified to be associated with a novel pathogenic variant c.942_943 + 3delinsCC in the AP4E1 gene. The patient manifested severely delayed psychomotor development, impaired global physical development and general illness. Movement disorders were evident during the neonatal period. Conclusions The present study identifies a previously unknown disease-inducing AP4E1 gene mutation.